2012
DOI: 10.1007/s13139-012-0128-x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Sarcoma and Acute Myelomonocytic Leukemia in an Adolescent with Tetrasomy 8: Staging with 18F-FDG PET/CT

Abstract: Tetrasomy 8 is a relatively rare chromosomal abnormality that has been reported in only 33 cases in hematologic disorders. It is known for its association with aggressive acute myeloid leukemia (AML) and myeloid sarcoma and is considered a very poor prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In 2005 Beyer et al reported a slight male gender predominance; in addition to MLL gene rearrangements described in 19 of the 103 published cases (16%) (9). Our literature search provided 11 new patients with MLL gene rearrangements, bringing the total to 30 cases out of 129 (23.2%) (9,(10)(11)(12)(13)(14). The high occurrence of MLL rearrangements possibly contributes to the adverse prognosis observed in patients with this genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005 Beyer et al reported a slight male gender predominance; in addition to MLL gene rearrangements described in 19 of the 103 published cases (16%) (9). Our literature search provided 11 new patients with MLL gene rearrangements, bringing the total to 30 cases out of 129 (23.2%) (9,(10)(11)(12)(13)(14). The high occurrence of MLL rearrangements possibly contributes to the adverse prognosis observed in patients with this genotype.…”
Section: Discussionmentioning
confidence: 99%
“…14 Long bone involvement usually occurs with multifocal bone involvement, and isolated humerus involvement on FDG PET/CT is rare. [15][16][17][18] Although 18 F-FDG PET/CT is not routinely used to evaluate myeloid sarcoma, it has been shown that FDG PET/CT is useful in disease assessment, staging, relapse detection, therapy response evaluation, and follow-up in myeloid sarcoma. 19,20 Myeloid sarcoma has moderate FDG uptake due to increased glycolytic activity with SUV max in the range of 2.6 to 9.7.…”
mentioning
confidence: 99%
“…Skeletal involvement occurs in 10%-12.5% of myeloid sarcoma cases, with the most common site of involvement being the axial bone 14. Long bone involvement usually occurs with multifocal bone involvement, and isolated humerus involvement on FDG PET/CT is rare [15][16][17][18]. Although 18 F-FDG PET/CT is not routinely used to evaluate myeloid sarcoma, it has been shown that FDG PET/CT is useful in disease assessment, staging, relapse detection, therapy response evaluation, and follow-up in myeloid sarcoma 19,20.…”
mentioning
confidence: 99%